Potential Effect of Averrhoa bilimbi (belimbing buluh) Marinades on Tenderizing the Buffalo Meat Compared to Actinidia chinensis (kiwifruit), Citrus limon (lemon) and Commercial Bromelain - Ismail, Mohamad Afifi; Chong, Gun Hean; Ismail-Fitry, Mohammad Rashedi (Journal of Science and Technology, 2018)
This study was conducted to analyze the effect of Averrhoa bilimbi (belimbing buluh) marinades versus other meat tenderizers on the physicochemical properties of buffalo meat. The buffalo meat chunks were marinated with 40% Averrhoa bilimbi, 40% Citrus limon, 40% Actinidia chinensis, 5% commercial bromelain meat tenderizer (positive control) and distilled water (negative control) for 24 hours at 4Â°C. The treated samples were cooked at 100Â°C for 20 minutes. Both raw and cooked samples were subjected to physicochemical analyses. There was significantly lower pH (p